Comparative Analysis of Tilt And Illumination of Solar Panels in the Design of Solar Test Simulator - Cholish; Hajar, Ibnu; Faza, Sharfina; Zumhari; Azis, Abdul; Abdulah (MultiTech Publisher, 2024)
In order for the designed tool to simulate solar panel measurements based on real-world conditions, the solar panel placement holder was arranged in a specific way during the design process. A monitor display that is mounted on the design will show the effectiveness of the solar panels and provide general solar panel information. Limitations in the positioning of solar panels will not provide a reference to conditions for measurement depending on the angle of incidence of the sun so further design needs to be done regarding the position of solar panels when measurements are taken. The development carried out in the design of this tool is in the form of adjusting the solar panel holder in the form of a solar panel holder tilt of 0°, 90°, 180°, and a distance of 30 cm halogen lamp as an energy source that is measured. Measurement results based on design, temperature 46°C, and 100% light.